Analisis Yuridis Peran Kantor Urusan Agama Dalam Mencegah Pernikahan Usia Dini Menurut Kompilasi Hukum Islam - Lukman Nul Hakim; Safrin Salam; Eko Satria (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
This study aims to analyze the role of the Office of Religious Affairs (KUA) in preventing early marriage based on the Compilation of Islamic Law and its implementation at the KUA of Sangia Wambulu District, Central Buton Regency. The study employed an empirical legal method with an empirical juridical approach. Data were collect ed through observation, interviews, documentation, and literature review, then analyzed descriptively and qualitatively. The findings show that the KUA performs its role through administrative examinat ion and age verification of prospective spouses, premarital guidance, legal counseling, and cooperation with village governments and comm unity leaders. These efforts are consistent with the Compilation of Islamic Law, Law Number 16 of 2019, and Minister of Religious Affa irs Regulation Number 34 of 2016. However, prevention effectiveness is still influenced by cultural factors, economic conditions, low educational attainment, and the high number of marriage dispensation requests. Therefore, stronger collaboration among the KUA, government, schools, religious leaders, and communities is needed to increase legal awareness and reduce early marriage in an integrated, sustainable, effective, consistent, and comprehensive manner.